PENGEMBANGAN MINAT DAN BAKAT ANAK MELALUI KEGIATAN SANGGAR SENI DAN IMPLIKASINYA TERHADAP PENDIDIKAN DASAR - Nur Wahyuni; Nurul Maulida; Anggi Nadilla; Nurul Nahwa Fadillah Nasution; Salsabillah Rahmadani; Vera Nika Br Tarigan; Sofia Handayani Harefa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the development of children's interests and talents through activities at Sanggar Deli Nusantara Jaya. The research uses a qualitative approach with a descriptive method. The research subjects consisted of trainers, parents, and children of studio participants. Data was collected through in-depth interviews, observations, and documentation. The results of the study show that the development of children's interests and talents takes place through a process of exploration, structured exercises, performance experiences, and parental support. A family studio environment forms children's confidence, discipline, responsibility, communication skills, and mental resilience. Internal factors such as motivation and curiosity as well as motivation and curiosity as well as external factors such as family support, coach coaching, and a conducive learning environment have a significant effect on the development of children's potential. This study concludes that collaboration between coaches, parents, and non-formal education environments plays an important role in optimizing the development of children's potential.